Facile Fabrication of Renewable Wood-Derived Carbon/SiBCN Aerogel Composites for High-Performance Microwave Absorption - Ke, Yuan; Han, Shangbo; Yang, LingYu; Chen, Xianqi; Hu, Peitao; Hong, Changqing; Dong, Shun (Journal of Composites and Biodegradable Polymers, 2025)
With the rapid development of communication technologies, there is an urgent demand for high-performance microwave absorbing materials. Wood-derived carbon (WDC), characterized by its lightweight, renewable, low-cost, and tunable dielectric properties, is regarded as a core candidate for future green microwave absorbing materials. However, pure WDC exhibits relatively limited microwave absorption performance. Thus, this work demonstrates a facile strategy for integrating WDC with SiBCN aerogels via controlled growth within the WDC matrix, achieved through a two-step sol-gel process combined with thermal treatment. SiBCN aerogel particles formed a typical three-dimensional network structure within the pores of WDC. The resulting WDC/SiBCN aerogel composite achieved a minimum reflection loss (RLmin) of -46.0 dB at a thickness of only 1.71 mm, with an effective absorption bandwidth (EAB) of 3.60 GHz, which demonstrates significantly enhanced microwave absorption performance compared to existing similar systems. The performance improvement is attributed to the synergistic effects of dipole polarization, multiple reflection mechanisms, and excellent impedance matching between the SiBCN aerogel and wood-derived carbon. This research provides a novel strategy for fabricating WDC/SiBCN aerogel composites that combine renewability with superior microwave absorbing capabilities.